Penerapan Konsep Sikap Kerja 5S pada Perpustakaan SMPN 023 Balikpapan Timur - Nadi Hernadi Moorcy; Putri Nuvira Mada; Dimas Rama Pramudia; Reza Putra Setya; Yoga Pamungkas; Arobby Mali; Natalia De Andrade Monis; Revina Ananda Isnaini; Muhammad Andri Taswin Nurdin; Tohap Prianto Gultom; Muhammad Zainudin Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Ignorance of the implementation of 5S has resulted in problems in the work environment. The community service program implemented at the State Middle School Library 023 East Balikpapan, Balikpapan City, has the aim of increasing productivity and comfort in a work environment that is always clean and spacious, reducing danger in the work environment so that the quality of the work environment is good and increasing savings by eliminating various waste in the work environment so as to create work effectiveness. In an effort to assist this community service activity, the method used involves observation, data collection and documentation. Implementation of activities is carried out through observation of daily work in the State Middle School Library 023 East Balikpapan to obtain sufficient data, then processed to prepare for structuring by involving students and teaching staff in implementing these activities. This method is used to identify problems in implementing 5S. Through the implementation of 5S, it is hoped that it will be able to provide an understanding of the importance of the 5S concept (Seiri, Seiso, Seiton, Sheiketsu, Shitsuke) and have a positive impact on optimizing the work environment.